COVID-19: factors causing hospitality worker's emotional job stress and the coping strategy used/ Arnieyantie A.H, Nadia Liana M.K and Wan Ezdriani W.A. - A.H, Arnieyantie; M.K, Nadia Liana; W.A, Wan Ezdriani (Universiti Teknologi Mara Selangor, 2022)
Despite the continued spread of the novel COVID-19, few investigations on the emotional stress caused by the pandemic have been done. This study investigated the factors causing hospitality workers to experience emotional job stress and how they cope. A semi-structured interview was applied to eight participants among the hotel kitchen staff. The thematic analysis discovered that work overload, unreasonable wages, and workflow changes are among the factors that caused the emotional stress working during the pandemic. Meanwhile, the coping strategies are making self-busy, involving family activities, and socializing on social media. Future studies should concentrate on what policymakers can do to support people in achieving good mental health.